Membrane electrode preparation method, product prepared by membrane electrode preparation method and application of product
By applying the catalyst layer on both sides of the proton exchange membrane and applying pressure to combine, the problems of membrane swelling and complex process in the preparation of membrane electrodes are solved, and the performance and production efficiency of membrane electrodes are improved.
Patent Information
- Application Number
- CN202310742011.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-24
AI Technical Summary
In the existing membrane electrode preparation methods, the direct coating method has defects such as membrane swelling problems and the coating is prone to cracks. However, the transfer method is difficult to meet the needs of improving fuel cell performance due to complex processes, disadvantages in terms of efficiency and cost.
By coating the anode and cathode catalyst layers on one side of the two proton exchange membranes, and combining the two proton membranes by applying pressure to form a tight membrane electrode, the membrane swelling problem is avoided, the process flow is simplified, and the two proton membranes are improved. Productivity and coating quality.
The performance improvement of the membrane electrode is achieved, the coating coverage rate reaches more than 99%, and the voltage value under the current density is above 0.36V under the condition of 2.2A/cm2, which simplifies the process flow, reduces costs, and improves production efficiency.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to a method for preparing a membrane electrode and products and applications prepared thereby. Background Art
[0002] The membrane electrode is the core component of the proton exchange membrane fuel cell, which consists of a proton exchange membrane, anode and cathode catalyst layers, and cathode and cathode gas diffusion layers. Usually, the preparation methods of membrane electrodes can be divided into two categories. One is the direct coating method, which is to directly coat or spray the catalyst ink onto the proton exchange membrane; the other is the transfer method, which is to first coat the catalyst ink onto a special transfer membrane, and then transfer it to the proton exchange membrane by hot pressing. With the development of fuel cell technology, the requirements for membrane electrode performance are getting higher and higher. The main factors affecting the performance of membrane electrodes include the formulation of the catalyst layer and the preparation process of the membrane electrode.
[0003] The direct coating method can improve the performance of membrane electrodes to a certain extent, but the direct coating process has membrane swelling problems, and the coating is prone to cracks and other defects. The transfer method for preparing membrane electrodes has high contact resistance and low performance because the catalyst layer and the proton membrane are in contact through transfer.
[0004] The traditional solution is to add a layer of support membrane to fix the proton membrane when coating the second side in direct coating to prevent the membrane from swelling during coating; the transfer method adds a layer of ionomer between the catalyst layer and the proton membrane. The ionomer is the same material as the proton membrane and can effectively reduce the contact resistance between the catalyst layer and the membrane material. The support membrane added in direct coating has high requirements for raw materials. The thickness cannot be too thin, otherwise it will not play a supporting role, and it cannot be too thick to affect heat transfer. At the same time, the support membrane is required to have moderate adhesion to the membrane material, which must have a certain adhesion but cannot bring down the catalyst layer on the first side. Adding a layer of ionomer in transfer printing makes the original method with more processes more complicated, and there are disadvantages in efficiency and cost.
[0005] CN113328106A discloses a fuel cell membrane electrode and its preparation method and application. The preparation method comprises the following steps: (1) preparing cathode catalyst slurry and anode catalyst slurry; (2) applying the cathode catalyst slurry to one side of the proton exchange membrane by the CCM method to obtain the cathode CCM; applying the anode catalyst slurry to one side of the anode gas diffusion layer to obtain the anode GDE; (3) stacking the cathode gas diffusion layer, the cathode CCM described in step (2) and the anode GDE in sequence, pressing them together to obtain the fuel cell membrane electrode. The direct coating method for preparing membrane electrodes can improve the performance of membrane electrodes to a certain extent, but the direct coating process has the problem of membrane swelling, and the coating is prone to cracks and other defects.
[0006] CN115312820A discloses a method for preparing a regional protective film by a coating method and a membrane electrode thereof, belonging to the field of preparation of fuel cell membrane electrodes. The method comprises the following steps: (1) primary coating and drying: coating a catalytic layer on the A side of a proton exchange membrane and performing drying treatment; (2) preparing a protective film; (3) rolling; (4) secondary coating and drying; (5) peeling; in the improved invention, when preparing the first catalyst layer, the other side of the proton exchange membrane is coated with a protective film, and a force is exerted on the proton exchange membrane to reduce swelling, but the requirements for the protective film are high, otherwise it cannot play a supporting role, and it is necessary to use any one or more combinations of UV glue, acrylic glue, organic silica gel, epoxy glue and polyurethane glue to prepare the protective film, the process is complicated, and the requirements for industrial production are high.
[0007] CN115064715A discloses an electrode CCM and a preparation method, a membrane electrode assembly MEA, and a fuel cell. The preparation method of the membrane electrode CCM includes the following steps: coating the first catalyst slurry and the second catalyst slurry on the first transfer substrate in sequence to obtain the first transfer substrate coated with the cathode catalyst layer; coating the first catalyst slurry on the second transfer substrate to obtain the second transfer substrate coated with the anode catalyst layer; using a thermal transfer process to thermally transfer the cathode catalyst layer to one side of the proton exchange membrane and the anode catalyst layer to the other side of the proton exchange membrane to obtain the membrane electrode CCM; adding a layer of ionomer during the transfer makes the original method with more steps more complicated, which has disadvantages in efficiency and cost.
[0008] In view of this, the present invention is proposed. Summary of the invention
[0009] One of the purposes of the present invention is to provide a method for preparing a membrane electrode. The method for preparing the membrane electrode comprises the following steps: coating the anode catalyst slurry and the cathode catalyst slurry on one side of two proton exchange membranes respectively; applying pressure to combine the two sides of the proton membranes that are not coated with the catalyst slurry to obtain the membrane electrode. The method for preparing the membrane electrode of the present invention is implemented using a traditional direct coating process without a transfer process, and there is no membrane swelling problem. It is simple to operate, has high production efficiency, and has excellent coating quality and membrane electrode performance.
[0010] The second object of the present invention is to provide a membrane electrode, the membrane electrode comprising an anode catalyst layer, a first proton exchange membrane, a second proton exchange membrane and a cathode catalyst layer; wherein the first proton exchange membrane and the second proton exchange membrane are combined by hot pressing. By hot pressing, the first proton exchange membrane and the second proton exchange membrane are tightly combined, and the membrane swelling problem will no longer occur between the two, and the membrane electrode finally obtained has excellent performance.
[0011] The third object of the present invention is a method for preparing a membrane electrode as described above, or the use of the membrane electrode in preparing a proton exchange membrane fuel cell. The method for preparing a membrane electrode described in the present invention and the membrane electrode prepared by the method can be used in preparing a proton exchange membrane fuel cell, providing a new preparation process for the preparation of exchange membrane fuel cells, playing a certain role in improving the coating quality, membrane electrode performance, etc., and can also effectively avoid the disadvantages of efficiency and cost in the preparation of fuel cells, and has obvious economic benefits and use value.
[0012] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0013] In a first aspect, the present invention provides a method for preparing a membrane electrode, the method comprising the following steps:
[0014] Coating: coating the anode catalyst slurry and the cathode catalyst slurry on one side of the two proton exchange membranes respectively;
[0015] Pressing: The membrane electrode is obtained by applying pressure to combine the two proton membranes at the sides not coated with the catalyst slurry.
[0016] In the present invention, an anode catalyst layer is coated on one side of a proton membrane, a cathode catalyst layer is coated on one side of another proton membrane, and then the other side of the proton membrane coated with the anode catalyst layer and the other side of the proton membrane coated with the cathode catalyst layer are bonded together by a certain pressure to form a membrane electrode (CCM), the CCM is composed of a proton membrane and anode and cathode catalyst layers located on both sides of the proton membrane, wherein the proton membrane is bonded together by two layers. The invention is implemented using a traditional direct coating process, does not go through a transfer process, and does not have a membrane swelling problem, is simple to operate, has high production efficiency, and has excellent coating quality and membrane electrode performance.
[0017] Preferably, the proton exchange membrane is selected from any one of perfluorosulfonic acid membrane, partially fluorinated sulfonic acid membrane, non-fluorinated sulfonic acid membrane or polyphenylimidazole membrane or a combination of at least two thereof.
[0018] Preferably, the thickness of the proton exchange membrane is 3-10 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc.
[0019] Preferably, a protective membrane is present on the side of the proton exchange membrane not coated with the catalyst slurry.
[0020] Preferably, the protective film is selected from any one of release polyethylene naphthalate, release polyethylene terephthalate, release polyethylene film or release polypropylene film, or a combination of at least two thereof.
[0021] Preferably, the solid content of the anode catalyst slurry and the cathode catalyst slurry is independently 8-20%, for example, it can be 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc.
[0022] Preferably, based on the total mass of the anode catalyst slurry being 100%, the anode catalyst slurry comprises, by mass percentage, 3-7% of catalyst, 5-13% of polymer binder, and 80-92% of solvent.
[0023] Taking the total mass of the anode catalyst slurry as 100%, the content of the catalyst is 3-7%, for example, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, etc.
[0024] Based on the total mass of the anode catalyst slurry as 100%, the content of the polymer binder is 5-13%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, etc.
[0025] Taking the total mass of the anode catalyst slurry as 100%, the content of the solvent is 80-92%, for example, 80%, 82%, 84%, 86%, 88%, 90%, 92%, etc.
[0026] Preferably, in the anode catalyst slurry, the catalyst is selected from carbon-supported platinum and / or platinum alloy, preferably any one of a Pt / C catalyst, a PtCo / C catalyst or a PtNi / C catalyst or a combination of at least two thereof.
[0027] Preferably, in the anode catalyst slurry, the polymer binder is any one of a perfluorinated sulfonic acid resin solution, a partially fluorinated sulfonic acid resin solution or a non-fluorinated sulfonic acid resin solution, or a combination of at least two thereof.
[0028] Preferably, in the anode catalyst slurry, the solvent includes alcohol and water.
[0029] Preferably, in the anode catalyst slurry, the mass ratio of alcohol to water is (1-5):(5-9);
[0030] Here, "1-5" can be, for example, 1, 2, 3, 4, 5, etc.;
[0031] Among them, "5-9" can be, for example, 5, 6, 7, 8, 9, etc.
[0032] Preferably, in the anode catalyst slurry, the alcohol is selected from any one of n-propanol, isopropanol, ethanol or glycerol, or a combination of at least two thereof, preferably n-propanol.
[0033] Preferably, based on the total mass of the cathode catalyst slurry being 100%, the cathode catalyst slurry comprises, by mass percentage, 3-7% of catalyst, 5-13% of polymer binder, and 80-92% of solvent.
[0034] Taking the total mass of the anode catalyst slurry as 100%, the content of the catalyst is 3-7%, for example, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, etc.
[0035] Based on the total mass of the anode catalyst slurry as 100%, the content of the polymer binder is 5-13%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, etc.
[0036] Taking the total mass of the anode catalyst slurry as 100%, the content of the solvent is 80-92%, for example, 80%, 82%, 84%, 86%, 88%, 90%, 92%, etc.
[0037] Preferably, in the cathode catalyst slurry, the catalyst is selected from carbon-supported platinum and / or platinum alloy, preferably any one of a Pt / C catalyst, a PtCo / C catalyst or a PtNi / C catalyst, or a combination of at least two thereof.
[0038] Preferably, in the cathode catalyst slurry, the polymer binder is any one of a perfluorinated sulfonic acid resin solution, a partially fluorinated sulfonic acid resin solution or a non-fluorinated sulfonic acid resin solution, or a combination of at least two thereof.
[0039] Preferably, in the cathode catalyst slurry, the solvent includes alcohol and water.
[0040] Preferably, in the cathode catalyst slurry, the mass ratio of alcohol to water is (1-5):(5-9);
[0041] Here, "1-5" can be, for example, 1, 2, 3, 4, 5, etc.;
[0042] Among them, "5-9" can be, for example, 5, 6, 7, 8, 9, etc.
[0043] Preferably, in the cathode catalyst slurry, the alcohol is selected from any one of n-propanol, isopropanol, ethanol or glycerol, or a combination of at least two thereof, preferably n-propanol.
[0044] In the present invention, when preparing anode catalyst slurry or cathode catalyst slurry, the polymer binder can be first dissolved in the solvent (alcohol and water) of part of the raw materials, and then mixed with the catalyst and the remaining solvent (alcohol and water) to ensure that the slurry is mixed more uniformly.
[0045] Preferably, the coating needs to be carried out in a vacuum environment with a vacuum degree of 0.01-0.098 MPa, for example, it can be 0.01 MPa, 0.02 MPa, 0.03 MPa, 0.04 MPa, 0.05 MPa, 0.06 MPa, 0.07 MPa, 0.08 MPa, 0.09 MPa, 0.098 MPa, etc.
[0046] Preferably, drying treatment is required after coating, and the drying temperature is 25-100°C, for example, it can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, etc.
[0047] Preferably, the thickness of the cathode catalyst layer formed after drying is 5-10 μm, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc.
[0048] Preferably, the thickness of the anode catalyst layer formed after drying is 1-5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc.
[0049] Preferably, the pressure is applied by hot pressing.
[0050] Preferably, the temperature of the hot pressing is 100-200°C, for example, it can be 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, etc.
[0051] Preferably, the hot pressing pressure is 0.5-1.5 MPa, for example, it can be 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, 1 MPa, 1.1 MPa, 1.2 MPa, 1.3 MPa, 1.4 MPa, 1.5 MPa, etc.
[0052] Preferably, the hot pressing time is 10s-10min, for example, it can be 10s, 20s, 30s, 40s, 50s, 60s, 2min, 4min, 6min, 8min, 10min, etc.
[0053] As a preferred technical solution of the present invention, the method for preparing the membrane electrode comprises the following steps:
[0054] (1) placing two proton exchange membranes in a vacuum environment with a vacuum degree of 0.01-0.098 MPa, coating an anode catalyst slurry on the unprotected membrane side of one of the proton exchange membranes, and coating a cathode catalyst slurry on the unprotected membrane side of the other proton exchange membrane, and then drying at 25-100° C. to obtain a proton exchange membrane with an anode catalyst layer and a proton exchange membrane with a cathode catalyst layer, respectively;
[0055] (2) After removing the protective membranes on one side of the proton exchange membrane with the anode catalyst layer and the proton exchange membrane with the cathode catalyst layer, the proton exchange membrane without the catalyst layer is placed opposite to each other, and hot-pressed for 10s-10min under the conditions of 100-200°C and 0.5-1.5Mpa. After hot-pressing, frames are attached around the anode catalyst layer and the cathode catalyst layer, and carbon paper is covered on the surfaces of the anode catalyst layer and the cathode catalyst layer, respectively, to obtain the membrane electrode.
[0056] In a second aspect, the present invention provides a membrane electrode, which is prepared by the preparation method described in the first aspect.
[0057] Preferably, the membrane electrode comprises an anode catalyst layer, a first proton exchange membrane, a second proton exchange membrane and a cathode catalyst layer; wherein the first proton exchange membrane and the second proton exchange membrane are combined by hot pressing.
[0058] In a third aspect, the present invention provides a method for preparing the membrane electrode as described in the first aspect, or use of the membrane electrode as described in the second aspect in preparing a proton exchange membrane fuel cell.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] (1) The membrane electrode preparation method of the present invention improves the traditional direct coating process. The anode catalyst slurry and the cathode catalyst slurry are respectively coated on one side of the two proton exchange membranes, and then pressure is applied to tightly combine the two proton exchange membranes, thereby avoiding the membrane swelling problem existing in the traditional direct coating process, so that the coating quality and membrane electrode performance are significantly improved; and the method is simple to operate as a whole, with high production efficiency, and avoids the problem of complex method caused by the use of thermal transfer process, and the disadvantages in efficiency and cost;
[0061] (2) The membrane electrode coating prepared by the method of the present invention has a coverage rate of more than 99% and a current density of 2.2A / cm 2 The voltage value under the conditions is above 0.36V, and the coating quality and membrane electrode performance are excellent. DETAILED DESCRIPTION
[0062] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0063] It should be noted that specific details are described in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0064] It should be noted that the directional words such as "upper", "lower", "left", "right", "front", "backward" and the restrictive words such as "first", "second" and the like described in the embodiments of the present invention are only used for the convenience of description and should not be construed as limiting the embodiments of the present invention. This is common knowledge in the art and will not be elaborated here.
[0065] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0066] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0067] The component proportions of the catalytic slurry used in the following examples and comparative examples are as follows:
[0068] ① Configuration of cathode catalytic slurry: Taking the total mass of the cathode catalytic slurry as 100%, the cathode catalytic slurry comprises, by mass percentage, 8% Pt / C, 4% perfluorosulfonic acid resin, 28% n-propanol and 60% water.
[0069] ② Configuration of anode catalytic slurry: Taking the total mass of the cathode catalytic slurry as 100%, the cathode catalytic slurry includes, by mass percentage, 10% Pt / C, 6% perfluorosulfonic acid resin, 14% n-propanol and 60% water.
[0070] Example 1
[0071] This embodiment provides a membrane electrode, which is prepared by the following method:
[0072] (1) Laying the first proton exchange membrane flat on a vacuum adsorption platform, the first proton exchange membrane is a perfluorosulfonic acid membrane with a thickness of 3 μm, evacuating the membrane, and maintaining the vacuum degree at 0.09 MPa, coating one side of the first proton exchange membrane with a cathode catalyst slurry with a coating thickness of 8 μm, and drying at 60° C. for 6 min to form a cathode catalyst layer;
[0073] The second proton exchange membrane is laid flat on the vacuum adsorption platform. The second proton exchange membrane is a perfluorosulfonic acid membrane with a thickness of 5 μm. The vacuum is evacuated to maintain a vacuum degree of 0.09 Mpa. The anode catalyst slurry is coated on one side of the second proton exchange membrane with a coating thickness of 3 μm. The coating is dried at 60° C. for 6 minutes to form an anode catalyst layer.
[0074] (2) The protective membrane on the other side of the first proton exchange membrane with the cathode catalyst layer is removed, and the protective membrane on the other side of the second proton exchange membrane with the anode catalyst layer is removed, and the first proton exchange membrane and the second proton exchange membrane without the catalyst layer are placed opposite to each other, and after hot pressing at a temperature of 160° C. and a pressure of 1 MPa for 5 min, the frames are attached around the first catalyst layer and the second catalyst layer, and carbon paper is covered on the surfaces of the cathode catalyst layer and the anode catalyst layer to form a membrane electrode assembly.
[0075] Example 2
[0076] This embodiment provides a membrane electrode, which is prepared by the following method:
[0077] (1) Laying the first proton exchange membrane flat on a vacuum adsorption platform, the first proton exchange membrane is a perfluorosulfonic acid membrane with a thickness of 3 μm, evacuating the membrane, and maintaining the vacuum degree at 0.09 MPa, coating one side of the first proton exchange membrane with a cathode catalyst slurry with a coating thickness of 8 μm, and drying at 60° C. for 6 min to form a cathode catalyst layer;
[0078] The second proton exchange membrane is laid flat on the vacuum adsorption platform. The second proton exchange membrane is a perfluorosulfonic acid membrane with a thickness of 8 μm. The vacuum is evacuated to maintain a vacuum degree of 0.09 Mpa. The anode catalyst slurry is coated on one side of the second proton exchange membrane with a coating thickness of 3 μm. The coating is dried at 60° C. for 6 minutes to form an anode catalyst layer.
[0079] (2) The protective membrane on the other side of the first proton exchange membrane with the cathode catalyst layer is removed, and the protective membrane on the other side of the second proton exchange membrane with the anode catalyst layer is removed, and the first proton exchange membrane and the second proton exchange membrane without the catalyst layer are placed opposite to each other, and after hot pressing at a temperature of 160° C. and a pressure of 1 MPa for 5 min, the frames are attached around the first catalyst layer and the second catalyst layer, and carbon paper is covered on the surfaces of the cathode catalyst layer and the anode catalyst layer to form a membrane electrode assembly.
[0080] Example 3
[0081] This embodiment provides a membrane electrode, which is prepared by the following method:
[0082] (1) Laying the first proton exchange membrane flat on a vacuum adsorption platform, the first proton exchange membrane is a perfluorosulfonic acid membrane with a thickness of 8 μm, evacuating the membrane, and maintaining the vacuum degree at 0.09 MPa, coating one side of the first proton exchange membrane with a cathode catalyst slurry with a coating thickness of 8 μm, and drying at 60° C. for 6 min to form a cathode catalyst layer;
[0083] The second proton exchange membrane is laid flat on a vacuum adsorption platform. The second proton exchange membrane is a partially fluorinated sulfonic acid membrane with a thickness of 8 μm. The membrane is evacuated to maintain a vacuum degree of 0.09 Mpa. The anode catalyst slurry is coated on one side of the second proton exchange membrane with a coating thickness of 3 μm. The membrane is dried at 60° C. for 6 minutes to form an anode catalyst layer.
[0084] (2) The protective membrane on the other side of the first proton exchange membrane with the cathode catalyst layer is removed, and the protective membrane on the other side of the second proton exchange membrane with the anode catalyst layer is removed, and the first proton exchange membrane and the second proton exchange membrane without the catalyst layer are placed opposite to each other, and after hot pressing at a temperature of 160° C. and a pressure of 1 MPa for 5 min, the frames are attached around the first catalyst layer and the second catalyst layer, and carbon paper is covered on the surfaces of the cathode catalyst layer and the anode catalyst layer to form a membrane electrode assembly.
[0085] Example 4
[0086] This embodiment provides a membrane electrode, which is prepared by the following method:
[0087] (1) Laying a first proton exchange membrane on a vacuum adsorption platform, wherein the first proton exchange membrane is a partially fluorinated sulfonic acid membrane with a thickness of 3 μm, evacuating the membrane to maintain a vacuum degree of 0.08 MPa, coating one side of the first proton exchange membrane with a cathode catalyst slurry with a coating thickness of 8 μm, and drying the membrane at 60° C. for 6 minn to form a cathode catalyst layer;
[0088] The second proton exchange membrane is laid flat on a vacuum adsorption platform. The second proton exchange membrane is a partially fluorinated sulfonic acid membrane with a thickness of 5 μm. The membrane is evacuated to maintain a vacuum degree of 0.08 Mpa. The anode catalyst slurry is coated on one side of the second proton exchange membrane with a coating thickness of 3 μm. The membrane is dried at 60° C. for 6 minutes to form an anode catalyst layer.
[0089] (2) The protective membrane on the other side of the first proton exchange membrane with the cathode catalyst layer is removed, and the protective membrane on the other side of the second proton exchange membrane with the anode catalyst layer is removed, and the first proton exchange membrane and the second proton exchange membrane without the catalyst layer are placed opposite to each other, and after hot pressing at a temperature of 100° C. and a pressure of 1.5 MPa for 10 seconds, the frames are attached around the first catalyst layer and the second catalyst layer, and carbon paper is covered on the surfaces of the cathode catalyst layer and the anode catalyst layer to form a membrane electrode assembly.
[0090] Example 5
[0091] This embodiment provides a membrane electrode, which is prepared by the following method:
[0092] (1) Laying the first proton exchange membrane flat on a vacuum adsorption platform, the first proton exchange membrane is a perfluorinated sulfonic acid membrane with a thickness of 3 μm, evacuating the membrane, and maintaining the vacuum degree at 0.05 MPa, coating one side of the first proton exchange membrane with a cathode catalyst slurry with a coating thickness of 8 μm, and drying at 60° C. for 6 min to form a cathode catalyst layer;
[0093] The second proton exchange membrane is laid flat on a vacuum adsorption platform. The second proton exchange membrane is a perfluorinated sulfonic acid membrane with a thickness of 5 μm. The membrane is evacuated to maintain a vacuum degree of 0.05 MPa. The anode catalyst slurry is coated on one side of the second proton exchange membrane with a coating thickness of 3 μm. The membrane is dried at 60° C. for 6 minutes to form an anode catalyst layer.
[0094] (2) The protective membrane on the other side of the first proton exchange membrane with the cathode catalyst layer is removed, and the protective membrane on the other side of the second proton exchange membrane with the anode catalyst layer is removed, and the first proton exchange membrane and the second proton exchange membrane without the catalyst layer are placed opposite to each other, and after hot pressing at a temperature of 200° C. and a pressure of 0.5 MPa for 10 min, the frames are attached around the first catalyst layer and the second catalyst layer, and carbon paper is covered on the surfaces of the cathode catalyst layer and the anode catalyst layer to form a membrane electrode assembly.
[0095] Example 6
[0096] This embodiment provides a membrane electrode, which is prepared by the following method:
[0097] (1) Laying the first proton exchange membrane flat on a vacuum adsorption platform, the first proton exchange membrane is a perfluorosulfonic acid membrane with a thickness of 3 μm, evacuating the membrane, and maintaining the vacuum degree at 0.09 MPa, coating one side of the first proton exchange membrane with a cathode catalyst slurry with a coating thickness of 8 μm, and drying at 60° C. for 6 min to form a cathode catalyst layer;
[0098] The second proton exchange membrane is laid flat on the vacuum adsorption platform. The second proton exchange membrane is a perfluorosulfonic acid membrane with a thickness of 5 μm. The vacuum is evacuated to maintain a vacuum degree of 0.09 Mpa. The anode catalyst slurry is coated on one side of the second proton exchange membrane with a coating thickness of 3 μm. The coating is dried at 60° C. for 6 minutes to form an anode catalyst layer.
[0099] (2) The protective membrane on the other side of the first proton exchange membrane with the cathode catalyst layer is removed, and the protective membrane on the other side of the second proton exchange membrane with the anode catalyst layer is removed, and the first proton exchange membrane and the second proton exchange membrane without the catalyst layer are placed opposite to each other, and after hot pressing at a temperature of 80° C. and a pressure of 1.8 MPa for 15 min, the frames are attached around the first catalyst layer and the second catalyst layer, and carbon paper is covered on the surfaces of the cathode catalyst layer and the anode catalyst layer to form a membrane electrode assembly.
[0100] Example 7
[0101] This embodiment provides a membrane electrode, which is prepared by the following method:
[0102] (1) Laying the first proton exchange membrane flat on a vacuum adsorption platform, the first proton exchange membrane is a perfluorosulfonic acid membrane with a thickness of 3 μm, evacuating the membrane, and maintaining the vacuum degree at 0.09 MPa, coating one side of the first proton exchange membrane with a cathode catalyst slurry with a coating thickness of 8 μm, and drying at 60° C. for 6 min to form a cathode catalyst layer;
[0103] The second proton exchange membrane is laid flat on the vacuum adsorption platform. The second proton exchange membrane is a perfluorosulfonic acid membrane with a thickness of 5 μm. The vacuum is evacuated to maintain a vacuum degree of 0.09 Mpa. The anode catalyst slurry is coated on one side of the second proton exchange membrane with a coating thickness of 3 μm. The coating is dried at 60° C. for 6 minutes to form an anode catalyst layer.
[0104] (2) The protective membrane on the other side of the first proton exchange membrane with the cathode catalyst layer is removed, and the protective membrane on the other side of the second proton exchange membrane with the anode catalyst layer is removed, and the first proton exchange membrane and the second proton exchange membrane without the catalyst layer are placed opposite to each other, and after hot pressing at a temperature of 220° C., a pressure of 0.4 MPa, and a time of 8 s, the frames are attached around the first catalyst layer and the second catalyst layer, and the surfaces of the cathode catalyst layer and the anode catalyst layer are covered with carbon paper to form a membrane electrode assembly.
[0105] Comparative Example 1
[0106] This comparative example provides a membrane electrode, which is prepared by the following method:
[0107] (1) Laying a 8 μm proton exchange membrane flat on a vacuum adsorption platform, evacuating the membrane to maintain a vacuum degree of 0.09 MPa, coating a first catalyst slurry on one side of the proton exchange membrane, and drying to form a cathode catalyst layer; removing the protective membrane on the other side of the proton exchange membrane, adsorbing the side of the proton exchange membrane coated with the cathode catalyst layer on the vacuum platform, coating a second catalyst slurry, and drying to obtain an anode catalyst layer, thereby obtaining a proton exchange membrane with a cathode catalyst layer on one side and an anode catalyst layer on the other side;
[0108] (2) The proton exchange membrane having a cathode catalyst layer on one side and an anode catalyst layer on the other side is subjected to hot pressing at a temperature of 160° C. and a pressure of 1 MPa for 5 min, and then frames are attached around the cathode catalyst layer and the anode catalyst layer, and carbon paper is covered on the surfaces of the cathode catalyst layer and the anode catalyst layer to form a membrane electrode assembly.
[0109] Performance Testing
[0110] Test samples: membrane electrodes provided in Examples 1-7 and membrane electrodes provided in Comparative Example 1;
[0111] Test items:
[0112] (1) Coating coverage: The obtained membrane electrode was photographed using a metallographic microscope, and the coating coverage was calculated by image processing to compare the coating quality;
[0113] (2) Voltage value: The prepared membrane electrode was tested with a test area of 25 cm 2 The test conditions are temperature 80℃, anode and cathode humidity 40% / 50%, anode and cathode metering ratio 1.9 / 1.5, anode and cathode back pressure 250 / 260Kpa, and the current density is recorded as 2.2A / cm 2 Voltage value under conditions;
[0114] The specific test results are shown in Table 1 below:
[0115] Table 1
[0116] test Coverage / % <![CDATA[Voltage / V @ 2.2 A / cm 2 > Example 1 99.76 0.408 Example 2 99.33 0.379 Example 3 99.04 0.362 Example 4 98.49 0.338 Example 5 96.32 0.354 Example 6 99.63 0.321 Example 7 99.68 0.336 Comparative Example 1 92.56 0.309
[0117] From the test data in Table 1, it can be seen that the membrane electrode coating coverage prepared by the method of the present invention reaches more than 98%, and the current density is 2.2A / cm 2 The voltage value under the conditions is above 0.32V, among which Example 1 is the most preferred technical solution, the coating coverage rate reaches above 99.7%, and the current density is 2.2A / cm 2 The voltage value under the condition is above 0.4V, which shows that the preparation method of the present invention, by coating the anode and cathode catalyst layers on one side of two proton exchange membranes respectively, and then hot pressing and bonding the two proton membranes together, to form a CCM does not have the problem of membrane swelling, is simple to operate, has high production efficiency, and has excellent coating quality and membrane electrode performance. Examples 6 and 7 change the hot pressing temperature. Although the coating quality, i.e., the coverage rate, is very high, the bonding force between the membranes is reduced due to too low a temperature, and the structure of the proton membrane is damaged due to too high a temperature, resulting in too high an ohmic impedance between the proton exchange membranes, and its electrochemical performance will also be reduced accordingly.
[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a membrane electrode, characterized in that: The method for preparing the membrane electrode comprises the following steps: The anode catalyst slurry and the cathode catalyst slurry are respectively coated on one side of the two proton exchange membranes; The membrane electrode is obtained by applying pressure to bond the two proton membranes at the sides not coated with the catalyst slurry.
2. The method for preparing a membrane electrode according to claim 1, characterized in that: The proton exchange membrane is selected from any one of perfluorosulfonic acid membrane, partially fluorinated sulfonic acid membrane, non-fluorinated sulfonic acid membrane or polyphenylimidazole membrane or a combination of at least two thereof; Preferably, the thickness of the proton exchange membrane is 3-10 μm; Preferably, a protective film is present on the side of the proton exchange membrane not coated with the catalyst slurry; Preferably, the protective film is selected from any one of release polyethylene naphthalate, release polyethylene terephthalate, release polyethylene film or release polypropylene film, or a combination of at least two thereof.
3. The method for preparing a membrane electrode according to claim 1 or 2, characterized in that: The solid content of the anode catalyst slurry and the cathode catalyst slurry is independently 8-20%; Preferably, based on the total mass of the anode catalyst slurry being 100%, the anode catalyst slurry comprises, by mass percentage, 3-7% of catalyst, 5-13% of polymer binder, and 80-92% of solvent; Preferably, in the anode catalyst slurry, the catalyst is selected from carbon-supported platinum and / or platinum alloy, preferably any one or a combination of at least two of a Pt / C catalyst, a PtCo / C catalyst or a PtNi / C catalyst; Preferably, in the anode catalyst slurry, the polymer binder is any one of perfluorinated sulfonic acid resin, partially fluorinated sulfonic acid resin or non-fluorinated sulfonic acid resin, or a combination of at least two thereof; Preferably, in the anode catalyst slurry, the solvent includes alcohol and water; Preferably, in the anode catalyst slurry, the mass ratio of alcohol to water is (1-5):(5-9); Preferably, in the anode catalyst slurry, the alcohol is selected from any one of n-propanol, isopropanol, ethanol or glycerol, or a combination of at least two thereof, preferably n-propanol.
4. The method for preparing a membrane electrode according to any one of claims 1 to 3, characterized in that: Taking the total mass of the cathode catalyst slurry as 100%, the cathode catalyst slurry comprises 3-7% of catalyst, 5-13% of polymer binder and 80-92% of solvent in terms of mass percentage; Preferably, in the cathode catalyst slurry, the catalyst is selected from carbon-supported platinum and / or platinum alloy, preferably any one or a combination of at least two of a Pt / C catalyst, a PtCo / C catalyst or a PtNi / C catalyst; Preferably, in the cathode catalyst slurry, the polymer binder is any one of perfluorinated sulfonic acid resin, partially fluorinated sulfonic acid resin or non-fluorinated sulfonic acid resin, or a combination of at least two thereof; Preferably, in the cathode catalyst slurry, the solid content of the polymer binder is 5-60%; Preferably, in the cathode catalyst slurry, the solvent includes alcohol and water; Preferably, in the cathode catalyst slurry, the mass ratio of alcohol to water is (1-5):(5-9); Preferably, in the cathode catalyst slurry, the alcohol is selected from any one of n-propanol, isopropanol, ethanol or glycerol, or a combination of at least two thereof, preferably n-propanol.
5. The method for preparing a membrane electrode according to any one of claims 1 to 4, characterized in that: The coating needs to be carried out in a vacuum environment with a vacuum degree of 0.01-0.098Mpa; Preferably, the coating needs to be dried at a temperature of 25-100°C; Preferably, the thickness of the cathode catalyst layer formed after drying is 5-10 μm; Preferably, the thickness of the anode catalyst layer formed after drying is 1-5 μm.
6. The method for preparing a membrane electrode according to any one of claims 1 to 5, characterized in that: The pressure is applied by heat pressing; Preferably, the temperature of the hot pressing is 100-200°C; Preferably, the hot pressing pressure is 0.5-1.5Mpa; Preferably, the hot pressing time is 10s-10min.
7. The method for preparing a membrane electrode according to any one of claims 1 to 6, characterized in that: The method for preparing the membrane electrode comprises the following steps: (1) placing two proton exchange membranes in a vacuum environment with a vacuum degree of 0.01-0.098 MPa, coating an anode catalyst slurry on the unprotected membrane side of one of the proton exchange membranes, and coating a cathode catalyst slurry on the unprotected membrane side of the other proton exchange membrane, and then drying at 25-100° C. to obtain a proton exchange membrane with an anode catalyst layer and a proton exchange membrane with a cathode catalyst layer, respectively; (2) After removing the protective membranes on one side of the proton exchange membrane with the anode catalyst layer and the proton exchange membrane with the cathode catalyst layer, the proton exchange membrane without the catalyst layer is placed opposite to each other, and hot-pressed for 10s-10min under the conditions of 100-200°C and 0.5-1.5Mpa. After hot-pressing, frames are attached around the anode catalyst layer and the cathode catalyst layer, and carbon paper is covered on the surfaces of the anode catalyst layer and the cathode catalyst layer, respectively, to obtain the membrane electrode.
8. A membrane electrode, characterized in that: The membrane electrode is prepared by the preparation method according to any one of claims 1 to 7.
9. The membrane electrode according to claim 8, characterized in that: The membrane electrode comprises an anode catalyst layer, a first proton exchange membrane, a second proton exchange membrane and a cathode catalyst layer; wherein the first proton exchange membrane and the second proton exchange membrane are combined by hot pressing.
10. A method for preparing a membrane electrode according to any one of claims 1 to 7, or use of the membrane electrode according to claim 8 or 9 in preparing a proton exchange membrane fuel cell.
